Analysis Of The 2nd Principle Of Pancasila On The Instagram Privacy Disclaimer - Dwipasari, Berlian; Ananta Saputra, Nicolas; Thalib, Emmy Febriani (Catuspata, 2024)
The article discusses the importance of user privacy on Instagram, a popular social media platform. In the digital era, millions of users share aspects of their personal lives, creating risks of data misuse and security threats. The right to privacy is recognized as a human right, including in the Indonesian Privacy Rights Law. Privacy Controls: Instagram gives users full control, allowing personal account settings. Data Policy: Instagram has a policy that explains the collection, use, and sharing of data, reflecting civilized principles. Data Security: Instagram claims to implement security measures and collaborate with third parties. Privacy Tools and Features: Instagram is constantly developing new privacy tools and features. In the context of Instagram user privacy, the principle of the 2nd Principle,